2019
DOI: 10.1073/pnas.1903461116
|View full text |Cite
|
Sign up to set email alerts
|

Distinct intraspecies virulence mechanisms regulated by a conserved transcription factor

Abstract: Tailoring transcriptional regulation to coordinate the expression of virulence factors in tandem with the core genome is a hallmark of bacterial pathogen evolution. Bacteria encode hundreds of transcription factors forming the base-level control of gene regulation. Moreover, highly homologous regulators are assumed to control conserved genes between members within a species that harbor the same genetic targets. We have explored this concept in 2 Escherichia coli pathotypes that employ distinct virulence mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…1A and B). Note that the protein-coding sequence of YhaJ is completely identical except for an amino acid substitution in UPEC, which we previously confirmed does not impact its apparent functionality (14). Despite this commonality, testing YhaJ expression revealed that YhaJ dosage varied drastically between strains grown in minimal essential medium (MEM), with UPEC for example displaying significantly (P ϭ 0.036) lower YhaJ expression than EHEC.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…1A and B). Note that the protein-coding sequence of YhaJ is completely identical except for an amino acid substitution in UPEC, which we previously confirmed does not impact its apparent functionality (14). Despite this commonality, testing YhaJ expression revealed that YhaJ dosage varied drastically between strains grown in minimal essential medium (MEM), with UPEC for example displaying significantly (P ϭ 0.036) lower YhaJ expression than EHEC.…”
mentioning
confidence: 59%
“…While condition-dependent binding sites were not unexpected, these data collectively reveal that the regulatory network of YhaJ is surprisingly heterogenous despite its highly conserved nature across the E. coli phylogeny. This suggests that strain-specific regulatory roles for YhaJ are potentially widespread in E. coli (5,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, several other TFs known to regulate std in S. Typhimurium were not important in S. Typhi, such as SeqA and StdE. The paper not only shows the complexity in which some of these promoters for important virulence factors are regulated, but also that assuming similar regulatory patterns for orthologous genes across even relatively similar bacteria is often incorrect, a concept I saw nicely exemplified by recent work by James Connolly (@RuaMicro) with Andy Roe (@DocAndy_J_Roe) at the University of Glasgow, UK, on the remarkable variability of binding sites for the Escherichia coli TF YhaJ across different, even relatively closely related strains of pathogenic E. coli [17,18].…”
Section: Accessmentioning
confidence: 99%
“…Pathogenic Escherichia coli also need to time the expression of toxins, colonization factors, and secretion systems as these molecules are immunostimulatory and incur a high energy cost ( Miao et al., 2010 ; Lee and Rietsch, 2015 ). Expression of these virulence factors are regulated at a transcriptional level ( Bustamante et al., 2001 ; Lee et al., 2012 ; Thomas and Wigneshweraraj, 2014 ; Crofts et al., 2018 ; Connolly et al., 2019 ) however, post-transcriptional regulation by small RNAs, RNA-binding proteins (RBPs) and ribonucleases are equally critical in modulating gene expression of stress response genes and virulence factors in response to rapid changes in the host environment. Each of these RNA regulators are described in more detail below.…”
Section: Introductionmentioning
confidence: 99%